Classification of endoscopic spine procedures - Mazda Farshad, MD; Christoph J. Laux, MD; Florian Wanivenhaus, MD; José M. Spirig, MD; Jonas Widmer, PhD; Michael Kelly, MD; Javier Quillo-Olvera, MD; Jin-Sung Kim, MD; Facundo van Isseldyk, MD; Sohrab Gollogly, MD; James Yue, MD; Xuexiao Ma, MD; et al. (North American Spine Society Journal, 2025)
ABSTRACT: Background: A consensus on grading the complexity of endoscopic spinal procedures is lacking, but urgently needed to guide training, clinical practice, and regulatory concepts. Methods: A 2-dimensional classification system was developed, considering both the technical and morphological parameters contributing to the complexity of endoscopic spine procedures. An international survey with 68 questions - including those on demographic data and surgical volumes, suitability of the proposed 2-dimensional classification system, and categories of techniques and morphologies - was completed by spine surgeons with endoscopic experience. A consensus was defined as a difference >/= 10% between the most frequently given grade and the second most given grade. In cases of no clear consensus (ie, agreement of less than 10%), an additional analysis considering only the responses from surgeons with experience of more than 500 endoscopic spine surgeries was performed. Results: 115 survey entries were received, of which 112 were analyzed. The participating spine surgeons (64% orthopedic surgeons, 35% neurosurgeons, 1% other) originated from 27 countries and have performed an average of 509 endoscopic spine surgeries (55,984 total endoscopic procedures). 85.7% of the survey respondents agreed that the proposed 2-dimensional classification system was indeed appropriate for its particular purpose. Thus, a consensus classification system was born, allowing for grading simple procedures (eg, Ia for lumbar interlaminar discectomy of a soft disc herniation) to complex procedures (eg, IIIc for revision posterior endoscopic cervical central decompression). Conclusions: A consensus of 112 endoscopic spine surgeons from 27 countries facilitated the development of a 2-dimensional classification system outlining the complexity of endoscopic spinal procedures, taking into account both technical aspects and morphological parameters. This classification system categorizes different endoscopic spine procedures and the pathologies they are employed to treat based on complexity, thus guiding the endoscopic spine community in medical training, patient education, and regulatory and reimbursement discussion.